Comparative analysis of drought stress-induced physiological and transcriptional changes of two black sesame cultivars during anthesis - Wang, Xiaohui; Wang, Min; Yan, Gui; Yang, Huiyi; Wei, Guangwei; Shen, Tinghai; Wan, Zehua; Zheng, Wei; Fang, Sheng; Wu, Ziming (Frontiers in Plant Science, 2023)
Sesame production is severely affected by unexpected drought stress during flowering stage. However, little is known about dynamic drought-responsive mechanisms during anthesis in sesame, and no particular attention was given to black sesame, the most common ingredient in East Asia traditional medicine. Herein, we investigated drought-responsive mechanisms of two contrasting black sesame cultivars (Jinhuangma, JHM, and Poyanghei, PYH) during anthesis. Compared to PYH, JHM plants showed higher tolerance to drought stress through the maintenance of biological membrane properties, high induction of osmoprotectants’ biosynthesis and accumulation, and significant enhancement of the activities of antioxidant enzymes. For instance, the drought stress induced a significant increase in the content of soluble protein (SP), soluble sugar (SS), proline (PRO), glutathione (GSH), as well as the activities of superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) in leaves and roots of JHM plants compared to PYH plants. RNA sequencing followed by differentially expressed genes (DEGs) analysis revealed that more genes were significantly induced under drought in JHM than in PYH plants. Functional enrichment analyses disclosed that several pathways related to drought stress tolerance, such as photosynthesis, amino acids and fatty acid metabolisms, peroxisome, ascorbate and aldarate metabolism, plant hormone signal transduction, biosynthesis of secondary metabolites, and glutathione metabolism, were highly stimulated in JHM than in PYH plants. Thirty-one (31) key highly induced DEGs, including transcription factors and glutathione reductase and ethylene biosynthetic genes, were identified as potential candidate genes for improving black sesame drought stress tolerance. Our findings show that a strong antioxidant system, biosynthesis and accumulation of osmoprotectants, TFs (mainly ERFs and NACs), and phytohormones are essential for black sesame drought tolerance. Moreover, they provide resources for functional genomic studies toward molecular breeding of drought-tolerant black sesame varieties.